School readiness and academic achievement of children with hearing impairment: A South African exploratory study - Ntsako P. Maluleke; Katijah Khoza-Shangase; Amisha Kanji (South African Journal of Childhood Education, 2021)
Background: Children with hearing impairment may be at risk of not achieving the necessary school readiness because of the link between hearing impairment and academic achievement. However, early hearing detection and intervention (EHDI) can improve potential outcomes for these children.